A Concordância verbal e suas repercussões avaliativas nas redações de vestibular - Padilha, Marisa [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This paper attempts to quantify the occurrences of verb agreement, as well as evaluative repercussions on a sample of one hundred and eight essays compiled by candidates entering the São Paulo State University- UNESP in 2006 through an annual entrance exam conducted by the Foundation and applied for Vestibular the Unesp - VUNESP in November 2005. Our reflections are observing about the possible relationships between the performances obtained in newsrooms observed (high, medium and low) and precepts found in the rules established by normative grammars. Our study is based on theoretical and methodological framework of variationist sociolinguistics and search through the quantification of data, discuss the factors that influence verb agreement in the corpus analyzed. Our results show not only a high index of cases of verbal agreement (standard variant) in the three types of essays analyzed, as well as cases of overcorrection that may be explained by the misapplication of the rules of agreement

O presente trabalho procura quantificar as ocorrências de concordância verbal, bem como suas repercussões avaliativas em uma amostra de cento e oito redações elaboradas por candidatos ao ingresso na Universidade Estadual Paulista- UNESP no ano de 2006 por meio do vestibular anual aplicado e realizado pela Fundação para o Vestibular da Unesp - VUNESP em novembro de 2005. Nossas reflexões partem da observação acerca das relações possíveis entre os desempenhos obtidos nas redações observadas (alto, médio e baixo) e os preceitos encontrados nas regras estabelecidas pelas gramáticas normativas. Nosso estudo fundamenta-se no arcabouço teórico-metodológica da sociolinguística variacionista e busca, através da quantificação dos dados, discutir os fatores condicionantes da concordância verbal no corpus analisado. Nossos resultados apontam não apenas para um alto índice de casos de concordância verbal (variante padrão) nos três tipos de redações analisadas, como também casos de hipercorreção que podem ser explicados pela aplicação equivocada das regras de concordância
Keywords: Concordancias; Sociolinguistica; Redação